Salivary D-dimer in pigs: Validation of an automated assay and changes after acute stress. (May 2020) - López-Martínez, M.J.; Escribano, D.; Contreras-Aguilar, M.D.; García-Martínez, J.D.; Martínez-Subiela, S.; Cerón, J.J.
Highlights: D-dimer was measured in porcine saliva with an automated immunoturbidimetric method. Acute stress induced by a nose snare significantly increased D-dimer in pig saliva. A significant correlation between D-dimer and alpha-amylase was found. Abstract: D-dimer is a peptide found in serum and is derived from the degradation of blood clots. Even though it has been analysed in human saliva, D-dimer has not been previously evaluated in the saliva of any veterinary species, and its source and role remain unknown. The objectives of this research were firstly, to validate the use of an automated method for the measurement of D-dimer in porcine saliva, and secondly, to evaluate whether D-dimer concentration changes in pig saliva after an acute stress stimulus. For this purpose, a complete analytical validation of a commercially-available immunoturbidimetric assay was carried out. In addition, an experimental acute stress model was induced in 11 pigs based on a technique involving restraint by nose-snare immobilisation for 1 min. Saliva samples were subsequently collected at different times and D-dimer, salivary alpha-amylase (sAA) and cortisol were assessed in order to evaluate changes in its concentrations after the stress induction. The D-dimer automated assay showed adequate reproducibility and sensitivity, with coefficients of variation below 10% and a limit of quantification of 0.167 μg/mL fibrinogen equivalent units (FEU). It also showed a high accuracy, determined by linearity under dilution and recovery tests. In the stress model, a significant increase ( P < 0.05) in salivary D-dimer 15 min after the stress stimulus and a positive correlation between D-dimer and sAA ( r = 0.51; P < 0.001) were observed. These results indicate that D-dimer can be measured in porcine saliva with an automated method and suggest that its concentration can be influenced by stressful conditions.